Results of limb reconstruction system in failed osteosynthesis of long bones - Kumar, Hiranya; Honnur, Siddalingeshwar Vithoba; Shukla, Manoj Kumar; Neruganti, Srikanth Etikala (International Journal of Research in Orthopaedics, 2017)
Background: The LRS is an excellent option treating the failed osteosynthesis in long bone fractures, because of failure in healing due to loosening of implant, infection, nonunion, poor bone quality and bone loss associated with deformities, limb length discrepancy, soft tissue problems, functional and financial issues. Methods: we prospectively treated 30 cases of failed osteosynthesis of long bones (7 plating, 22 nailing & 1 k-wire with plaster) between April 2009 to October 2015 with LRS. Initially we managed by implant removal, freshening of fracture site or radical debridement followed by LRS application. Results: Union occurred in 93% cases. The eradication of infection was seen in 96.5% cases. Average lengthening done was 4.2 cms. We had 93% excellent and 7 % poor bony result. Functional result was excellent in 45%, good in 48% and failure in 7% cases using ASAMI scoring system. Conclusions: LRS is an excellent option in the management of failed osteosynthesis especially associated with infection, nonunion, deformities, limb length discrepancy, soft tissue problems, functional and financial issues and also where re-osteosynthesis is challenging with poor bone quality and bone stock. It is simpler technically, patient friendly and short learning curve.